THE STUDENTS' LEARNING STYLE FOR MACROECONOMIC THEORY COURSES IN ECONOMIC EDUCATION STUDY PROGRAM OF PAMULANG UNIVERSITY - Syafaatul Hidayati; Badrus Sholeh; Syamsul Anwar (PEKA, 2024)
The purpose of this study is to find out the learning style of students in learning macroeconomic theory courses in the economic education study program, Pamulang university. This research is a descriptive quantitative research with the method used is the survey method. The samples used were non-probability sampling methods. The selected participants are students who have taken macroeconomic theory courses in the economic education study program at the University of Pamulang. The students who filled out the questionnaire were 27 students. Filling is done through the google form link. Furthermore, the existing research data is analyzed in a qualitative descriptive manner. The results of the study showed that the learning style of students of the Economics Education study program at Pamulang University was still more dominant visually by 37%, followed by reading/writing by 33.3%, auditory by 14.8%, and kinesthetics by 14.8%. By knowing a person's learning style, lecturers should be able to determine the right steps during the lecture activities that will be carried out.